Mechanical inefficiency of the thoracic cage in scoliosis. Issue 6 (June 1981) - Jones, R S; Kennedy, J D; Hasham, F; Owen, R; Taylor, J F
Abstract : The mechanism of impairment of ventilatory function in idiopathic scoliosis has been studied in 23 children, all girls, and compared with 27 normal children and 24 normal young adult females. The vital capacity, FEV 1, gas transfer factor, and the maximum static expiratory airway pressure were all significantly reduced. total lung capacity and the maximum inspiratory pressure were lower than in the normal subjects, but the difference was not significant. Restriction of thoracic cage movement by a belt showed that the thorax in the children with scoliosis was as mobile as in the normal subjects. The results are explained in terms of the characteristic deformity in scoliosis which causes one hemi-thorax to become relatively smaller than the other. It is concluded that this causes an inherent mechanical inefficiency of ventilation which is likely to contribute to respiratory failure in these subjects.